Nickel-Titanium self-knotting suture wire for deep surgical field: A validated numerical model. (September 2020) - Berti, Francesca; Nespoli, Adelaide; Villa, Elena; Dallolio, Villiam; Passaretti, Francesca; Pennati, Giancarlo; Migliavacca, Francesco; Petrini, Lorenza
Abstract: The aim of this work is to set a finite element model of a Ni-Ti self-knotting suture, designed for deep neurosurgical applications, and to provide a reliable tool for evaluating its functionality before entering clinical practice. A closed shape is memorized through specific heat treatments; once implanted in the open configuration the surgeon does not need to pack any knots since the suture closes by itself only using some drops of physiological solution. A material user-subroutine allows the modeling of the shape memory effect which governs its functionality. Experiments of increasing complexities, involving shape-recovery behavior, are designed to validate the model. Indeed, accordingly with the most recent Standards, validation is the fundamental step for allowing the use of numerical models for predicting device performance and taking a decision on the design that may affect patient safety or health. Herein, once validated, the numerical approach is used for investigating the effects of the device preparatory phase on the clinical performance.